1995
DOI: 10.1128/iai.63.9.3705-3710.1995
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of human and porcine intestinal spirochetes in one-day-old specific-pathogen-free chicks: an animal model of intestinal spirochetosis

Abstract: One-day-old chicks were infected orally with two strains of weakly hemolytic spirochetes isolated from a human and a pig with intestinal spirochetosis. These spirochetes both colonized birds, attached end-on to their cecal enterocytes, induced watery diarrhea, and significantly depressed growth rates. Cultures of Serpulina innocens failed to colonize the chicks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
41
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 30 publications
8
41
0
Order By: Relevance
“…In the literature, the same histological features described for human IS were found in animal models of human IS (weaned pigs, 1-day-old chicks) and in cases of spirochetosis in pigs, dogs and poultry. 8,31 Concerning the histological aspects of human IS described in the literature, our results confirmed the role of histology in recovering spirochetes and in the description of the possible pathogenicity of the microorganisms, because in all cases we reported that active colitis was evident. In accordance with other reports in the literature, 4,12,13,29,30,35 our study suggested a possible pathogenetic mechanism based on the extension of Brachyspira presence in all segments of the colon, evidence of the progressive destruction of microvilli with direct contact between the bacteria and the cell membrane, and presence of colitis with inflammatory infiltrate and sometimes cryptitis.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In the literature, the same histological features described for human IS were found in animal models of human IS (weaned pigs, 1-day-old chicks) and in cases of spirochetosis in pigs, dogs and poultry. 8,31 Concerning the histological aspects of human IS described in the literature, our results confirmed the role of histology in recovering spirochetes and in the description of the possible pathogenicity of the microorganisms, because in all cases we reported that active colitis was evident. In accordance with other reports in the literature, 4,12,13,29,30,35 our study suggested a possible pathogenetic mechanism based on the extension of Brachyspira presence in all segments of the colon, evidence of the progressive destruction of microvilli with direct contact between the bacteria and the cell membrane, and presence of colitis with inflammatory infiltrate and sometimes cryptitis.…”
Section: Discussionsupporting
confidence: 82%
“…This was associated with various symptoms and has since then been described by many authors. [1][2][3][4][5][6][7][8][9][10][11][12]24,[29][30][31][32] Since 1997, Brachyspira spp. has been included in the list of human enteropathogenic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Similar colonization has been reported for human and porcine strains of S. pilosicolz in naturally occurring cases of IS, and in experimental infections of 1-d-old SPF chicks (Dwars et nl. 1992a;Trott et al 1995). Strains of S. pilosicoli therefore infect wild birds and potentially may be a source of infection to other species, including humans.…”
Section: Three Major Divisions Within This Group (Et II E T Iii Andmentioning
confidence: 99%
“…11 There also have been studies in which intestinal spirochete strains isolated from humans have been used to infect and cause intestinal disease in chickens and pigs. 12,13 In contrast, in studies where colonic specimens or feces of a large series of patients were assessed, IS was a frequent finding, ranging from 1.9 to 50%, 3,10,11,[14][15][16][17] being particularly common in developing communities. 3,10,11,18,19 In some studies symptoms were not modified by IS eradication, [14][15][16][17] leading to the suggestion that intestinal spirochetes are harmless commensals in humans, and thus specific treatment is not required.…”
Section: Introductionmentioning
confidence: 99%